Development of Storyboard Media to Improve Storytelling Skills on The Material Plant Breeding in Elementary School - Turwati, Turwati; Retno Susanti; Siti Dewi Maharani (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2022)
The world of education today is developing so fast. Students are required to be able to master skills, one of which is storytelling skills. Students' low skills in storytelling are one of the consequences of implementing online learning so far. The purpose of this study is to regenerate and improve storytelling skills in grade VI students at SDN 21 Muara Telang, especially in Plant Breeding material. This research is a research and development (R&D) research that produces products in the form of learning media in the form of storyboards that are tested for effectiveness to increase students' ability to tell stories. The model used in this study is the ADDIE maodel, where the stages include: analysis, design, development, implementation and evaluation. The result of this study is the production of a product in the form of storyboard media that is proven to improve storytelling skills in grade VI students at SDN 21 Muara Telang, Banyuasin regency.